The construction of the concepts of south-alternity and geopolitics in the Caribbean (2019)
Studies on Geopolitics have been characterized by state-centered constructions that limit scope to rigid conditions in the classical configuration between space and power. Although there has been a critical advance around the concept with new epistemological contributions, notions about it in peripheral areas such as the Caribbean are conceived as terminological legacies and do not correspond to the particular essence of the contexts and realities. In this sense, there is a need to generate own knowledge regarding Geopolitics from the Caribbean instead of the Caribbean. Additionally, the construction of a concept of south-alternate on said area to achieve an epistemological foundation of its own and that detaches itself from categorical legacies. For this reason, this article seeks to answer the question about how have the concepts of south-alternity and geopolitics been built in the Caribbean. © 2019 Universidade de Lisboa.